Checking the possibility of equating a mathematics assessment between Russia, Scotland and England for children starting school. Issue 2 (4th March 2018) - Ivanova, Alina; Kardanova, Elena; Merrell, Christine; Tymms, Peter; Hawker, David
Abstract: Is it possible to compare the results in assessments of mathematics across countries with different curricula, traditions and age of starting school? As part of the iPIPS project, a Russian version of the iPIPS baseline assessment was developed and trial data were available from about 300 Russian children at the start and end of their first year at school. These were matched with parallel data from representative samples of equal numbers of children from England and Scotland. The equating of the scales was explored using Rasch measurement. A unified scale was easiest to create for England and Scotland at the start and end of their first year at school when children only differ by a half a year in age, and live in adjacent countries with a common language. Although fewer items showed invariance across the three countries, it was possible to link iPIPS scores in mathematics from the start and end of the first year at school across Scotland, England and Russia. The findings of this study suggest that, despite the apparent difficulties, meaningful comparisons of mathematics attainment and development can be made. These will allow for substantive interpretations with policy implications.